MODEL DATA ENVELOPMENT ANALYSIS (DEA) DALAM MANAJEMEN OPERASI - Meilisa Malik; Tantri Octora Dwi Syah Putri (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
Quality management is an effective system in operation management to develops, maintains, and improves quality from groups of companies that allow marketing, production, and service at the most economycal level as well as ensuring customer satisfication. Many companies are practicing quality management to improve their bussiness performance. One of performance measurement is through measurement of efficiency. One of the tools can be used to assess efficiency of companies performance is Data Envelopment Analysis (DEA). The aim of this paper is using Data Envelopment Analysis (DEA) model to assess efficiency of quality management. In this paper will be explained CCR, and BCC models to assess efficiency of quality management. From the example of problem given, it’s proven that DEA is a reliable method for modeling operation process with multiple input and multiple output from a set of Decission Making Units (DMU), and then measure its efficiency both financially and nonfinancially.